Z-type heterojunction difunctional composite photocatalyst NDI / PTA as well as preparation and application thereof
By combining NDI and PTA organic semiconductor catalysts to form a Z-type heterojunction structure, the problem of inefficiency in visible light response of existing photocatalysts is solved, and efficient photocatalytic decomposition of water and antibiotic degradation is achieved.
Patent Information
- Application Number
- CN202510052756.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-14
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2045-01-14
AI Technical Summary
Existing photocatalysts have problems with low efficiency and low charge separation/transmission efficiency in terms of visible light response, making it difficult to effectively decompose water to produce hydrogen and degrade antibiotics.
By combining the two organic semiconductor catalysts, naphthimide (NDI) and perylene tetracarboxylic acid (PTA), the Z-type heterojunction structure is formed, and the efficiency of photocatalytic decomposition of water and antibiotics is improved by using the stacking of their π planes and the built-in electric field.
Efficient photocatalytic decomposition of water to produce hydrogen and antibiotic degradation were achieved. The photocatalytic hydrogen evolution rate of 8% NDI/PTA reached 45.59 mmol/g/h, the apparent quantum efficiency reached 3.16%, and the degradation rate of antibiotics exceeded 80%.
Smart Images

Figure CN119909752A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the preparation and application of a Z-type heterojunction visible light responsive bifunctional organic composite catalyst NDI / PTA, and specifically to the preparation of a Z-type heterojunction visible light responsive bifunctional organic composite catalyst NDI / PTA and its application in photocatalytic water decomposition to produce hydrogen and ofloxacin, tetracycline hydrochloride, and sulfamethoxazole antibiotic degradation. The composite photocatalyst is applied to the photocatalytic water decomposition to produce hydrogen and ofloxacin, tetracycline hydrochloride, and sulfamethoxazole antibiotic degradation. Photocatalytic water decomposition to produce hydrogen shows a high photocatalytic water decomposition to produce hydrogen rate. The photocatalytic H2 evolution rate of 8% NDI / PTA reaches 45.59 mmol / g / h, which is 2.73 times that of single PTA and 45.59 times that of single NDI. At the same time, at a wavelength of 450nm, the apparent quantum efficiency (AQY) of 8% NDI / PTA reaches 3.16%. In addition, the photocatalytic degradation rates of ofloxacin (OFL) and tetracycline hydrochloride (TC-HCl) by 8% NDI / PTA were both over 80% within 90 min. Finally, the intermediate products of OFL after degradation were determined and possible degradation pathways were proposed. Background Art
[0002] Energy crisis and environmental pollution are two major problems brought about by the rapid development of global economy and society. Semiconductor photocatalysis technology with the ability to utilize solar energy has been widely regarded as an ideal way to solve these problems.
[0003] Since the UV spectrum accounts for less than 5% of the total solar energy, commercially viable visible light-active photocatalysts are urgently needed. To achieve response to visible light, the band gap needs to match the energy of visible light, generally between 1.8eV and 3.2eV. However, the band gaps of many common semiconductor materials are either too large to be excited by visible light, or too small, resulting in most semiconductors not being able to meet the overpotential for hydrogen production or redox reactions of organic pollutants. Therefore, only a few visible light-responsive photocatalysts can achieve photocatalytic water decomposition for hydrogen evolution or degradation of organic pollutants.
[0004] In the actual reaction process, photogenerated electrons and holes are easy to recombine instead of participating in the redox reaction on the surface of the photocatalyst, resulting in low photocatalytic efficiency, which seriously limits further practical applications. Therefore, improving the charge separation / transfer efficiency is a key scientific issue to improve the efficiency of photocatalysis. Inorganic semiconductors are common photocatalysts for photocatalytic water decomposition. Various inorganic semiconductor photocatalysts have been developed, such as metal-based sulfides, oxides, nitrides, carbides, and perovskites.
[0005] In recent years, organic semiconductors composed of elements such as C, H and O, which are abundant on Earth, have attracted much attention due to their excellent structural adjustability, which can be used to adjust their absorption spectra and photoelectric properties, thereby improving their oxidation or reduction capabilities. In addition, organic semiconductors have shown better processability due to their inherent flexibility.
[0006] Currently, organic catalysts such as covalent organic frameworks (COFs), hydrogen-bonded organic frameworks (HOFs), conjugated microporous polymers (CMPs), and metal-organic frameworks (MOFs) have been developed. Among them, perylene series materials and their derivatives have attracted widespread attention due to their good thermal stability, excellent optics, carrier transport properties, light transmittance, mechanical stability, and good visible light capture performance. Therefore, they have been applied to photocatalytic water reduction / oxidation, organic photovoltaic devices, H2O2 preparation, photocatalytic degradation, disinfection and other fields. However, the exciton diffusion length in organic photocatalysts is shorter than that in inorganic photocatalysis, and the difficulty in exciton separation makes it difficult to dissociate into unbound charge carriers and the driving force for photogenerated charge separation is insufficient, which seriously affects the photocatalytic activity.
[0007] However, there are few reports on Z-type heterojunction photocatalysts based on perylene planar material PTA. Therefore, the co-assembly of aromatic compounds with electron defects, such as naphthalene imide (NDI) and perylene tetracarboxylic acid (PTA), which have excellent light harvesting ability, good carrier mobility and excellent thermal stability, was used to construct an effective Z-type interface electron transfer channel. There is a huge built-in electric field in this channel, thus achieving efficient and stable photocatalytic water decomposition to produce hydrogen and antibiotic degradation. Summary of the invention
[0008] The purpose of the present invention is to compound two organic semiconductor catalysts, NDI and PTA, to obtain a novel composite catalyst NID / PTA. The composite catalyst has dual functions. Due to the stacking of its π plane, the electrons are unevenly distributed, so that it has a large dipole moment, thereby generating a strong built-in electric field, so that water can be efficiently photocatalytically decomposed to produce hydrogen, and ofloxacin, tetracycline hydrochloride and sulfamethoxazole in antibiotics can also be efficiently degraded.
[0009] Technical solution of the present invention
[0010] The preparation method of NID / PTA composite photocatalyst has the following specific steps:
[0011] (1) The specific process of preparing PTA: using 3,4,9,10-perylenetetracarboxylic acid dianhydride, potassium hydroxide and glacial acetic acid as raw materials, the organic semiconductor 3,4,9,10-perylenetetracarboxylic acid (PTA, or 3,4,9,10-perylenetetracarboxylic acid) was prepared by alkaline hydrolysis and acidic self-assembly;
[0012] 1) Weigh 35.0-60.0 mg (preferably 35.0-60.0%, more preferably 40.0-55.0%, and optimally 47.0-52.0%) of 3,4,9,10-perylenetetracarboxylic dianhydride in a container, add 150.0-300.0 ml of ultrapure water, and ultrasonicate for 30.0-60.0 min at an ultrasonic amplitude of 40.0-100.0 Hz; 2) Weigh 350.0-650.0 mg (preferably 400.0-600.0 mg, more preferably 450.0-550.0 mg, and optimally 490.0-510.0 mg) of potassium hydroxide and add them to the above ultrasonicated solution. ; Stir it at 40.0-55.0℃ for 4.0h to obtain a PTA precursor; 3) Add 350.0-650.0μl (preferably 400.0-600.0μl, more preferably 450.0-550.0μl, optimally 490.0-510.0μl) of glacial acetic acid to a container containing 50.0-100.0ml of water; 4) Add the PTA precursor obtained in step 2) after alkaline hydrolysis with potassium hydroxide to the glacial acetic acid solution obtained in step 3), and obtain PTA after 6.0-10.0h of acidic self-assembly; 5) Solid-liquid separation, wash the solid with water, and dry it to obtain PTA.
[0013] (2) Preparation of composite catalyst NDI / PTA (1,4,5,8-naphthalenetetracarboxylic acid diimide / 3,4,9,10-perylenetetracarboxylic acid): 1) Weigh 35.0-60.0 mg (preferably 35.0-60.0%, more preferably 40.0-55.0%, and optimally 47.0-52.0%) of 3,4,9,10-perylenetetracarboxylic acid dianhydride in a container, add 150.0-300.0 ml of ultrapure water, and ultrasonically 30.0-60.0min, ultrasonic amplitude 40.0-100.0Hz; 2) weigh 400.0-600.0mg (preferably 400.0-600.0mg, more preferably 450.0-550.0mg, optimally 490.0-510.0mg) of potassium hydroxide and add it to the above ultrasonic solution; stir it at 40.0-55.0℃ for 2.0-4.0h to obtain a precursor of PTA 3) weighing 1.0-15.0 mg of NDI (1,4,5,8-naphthalenetetracarboxylic acid diimide) (preferably 1.0-15.0 mg, more preferably 1.5-9.0 mg, optimally 1.85-2.5 mg) and adding it to a solution containing 490.0-510.0 μl (preferably 400.0-600.0 μl, more preferably 450.0-550.0 μl, optimally 490.0-510.0 μl) of glacial acetic acid 5) Add 50.0-100.0ml of water into a container and perform ultrasound for 1.0-2.0h with an ultrasound amplitude of 40-100Hz to obtain an acidic NDI aqueous solution; 4) Add a PTA precursor into the acidic NDI aqueous solution and stir at 35.0-45.0℃ (preferably 35.0-45.0℃, optimally 37.0-42.0℃) for 6-10h; 5) Separate the solid from the liquid, wash the solid with water, and dry to obtain an NDI / PTA composite catalyst.
[0014] The 8% NDI / PTA composite photocatalyst was used in the photocatalytic water decomposition reaction to produce hydrogen.
[0015] Test conditions: The photocatalytic hydrogen evolution performance of the sample was tested in a glass-enclosed gas system (Labsolar-6A, Beijing Perfectlight). 9.0-15.0 mg (preferably 5.0-13 mg, optimally 9.0-11.0 mg) of photocatalyst powder was ultrasonically dispersed in 100.0 mL of deionized water. Chloroplatinic acid (H2PtCl6·6H2O) was photocatalytically oxidized to Pt as a co-catalyst on the sample surface by an in-situ photodeposition method, with a co-catalyst loading of 1.0-8.0 mg (preferably 1.0-8.0 mg, optimally 3.0-7.0 mg). 0.15-0.3 M ascorbic acid (AA) was used as a sacrificial agent, and chloroplatinic acid (H2PtCl6·6H2O) was photocatalytically oxidized to Pt as a co-catalyst on the sample surface by an in-situ photodeposition method. A 300 W xenon lamp visible light was used as the light source (420<λ<780 nm). The generation of H2 was detected at given time intervals by an online gas chromatograph (TCD detector, Ar carrier, 5 μm molecular sieve column). Hydrogen evolution experiments with different NDI loadings (preferably 1.0-15.0 mg, more preferably 1.5-9.0 mg, and optimally 1.85-2.5 mg), different Pt loadings (preferably 1.0-8.0 mg, and optimally 3.0-7.0 mg), and optimal catalyst dosage (preferably 5.0-13 mg, and optimally 9.0-11.0 mg) were studied.
[0016] The apparent quantum yield (AQY) of different monochromatic lights (365 nm, 400 nm, 450 nm, 500 nm, 550 nm, 600 nm, 650 nm and 700 nm) was measured under different bandpass filters (FWHM = 15 nm). The irradiation area was 1.0 cm -2 (300W xenon lamp, PerfectLight). The average intensity was determined by an optical power meter (PL-MW2000). 10 mg of photocatalyst was used. AQY was calculated according to the following formula, taking monochromatic light of 450 nm as an example:
[0017]
[0018] The 8% NDI / PTA composite photocatalyst was used for the photocatalytic degradation of the antibiotics ofloxacin, tetracycline hydrochloride, and sulfamethoxazole.
[0019] Test conditions: A 300W xenon lamp (420<λ<780nm) was used for photocatalytic degradation research. The photocatalytic degradation reaction was carried out in a double-jacketed quartz tube reactor with 5.0-13.0mg (preferably 5.0-13mg, optimal 9.0-11.0mg) of photocatalyst and 100mL of antibiotic solution 10.0-50.0mg / L (preferably 10.0-40.0mg / L, more preferably 17.0-30mg / L, optimal 20.0-25.0mg). The reaction temperature was maintained at 20-25°C by a circulating cooling water system. Before light irradiation, the suspension was stirred in the dark for 30 minutes to reach adsorption-desorption equilibrium. The solution was taken every 10min and passed through a needle filter (13mm, 0.54μm) to obtain the supernatant, which was analyzed by liquid ultraviolet (UV-VIS SPECTROPHOTOMETER T9) to obtain the degradation rate.
[0020] The advantages of the present invention are: a catalyst of a Z-type heterojunction structure is formed by using organic semiconductors NDI and PTA, and Pt is used as a co-catalyst of the photocatalyst. An organic composite photocatalyst NDI / PTA is prepared, and its preparation method is simple, the reserves are abundant, and the cost is low. Through the photocatalytic hydrogen production test, it is known that under the optimal conditions (the mass loading of NDI is 8%, the mass loading of the co-catalyst Pt is 5%, and the optimal catalyst dosage is 2 mg), the photocatalytic hydrogen production activity of 8% NDI / PTA is 45.56 mmol / g / h, which is 45.56 times the activity of single NDI photocatalytic decomposition of water to produce hydrogen, and 2.73 times that of single PTA. The apparent quantum efficiency (AQY) reaches 3.16% (monochromatic light is 450nm). In addition, after 90 minutes of degradation, the removal rate of OFL by 8% NDI / PTA reaches 81%, and the degradation rate (0.021min -1 ) is NDI (0.0006min -1 ) is 35 times that of PTA (0.01min -1 ) was 2.1 times higher than that of 8% NDI / PTA. The removal rate of TC-HCl by 8% NDI / PTA also reached 86.5%, and the degradation rate (0.018min -1 ) is NDI (0.0001min -1 ) is 180 times that of PTA (0.014min -1 ) is 1.3 times of that of the photocatalyst. The photocatalyst can also degrade SMX. Within 90 minutes, the removal rate of 8% NDI / PTA is 21%, and the degradation rate (0.0026min -1 ) is NDI(0.0002min -1 ) is 13 times that of PTA (0.0013min -1 Finally, the intermediate products of OFL were determined, and the possible degradation pathways of OFL were given.
[0021] The organic composite photocatalyst NDI / PTA of the present invention exhibits excellent redox performance, and the composite catalyst has the advantages of simple preparation method, low cost, reusability, greenness, and good photocatalytic efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 Example 2 Organic composite catalyst x% NDI / PTA synthesis route
[0023] Figure 2 . XRD patterns of NDI, PTA, and x% NDI / PTA composite photocatalysts in Examples 1 and 2;
[0024] Figure 3 . FT-IR images of NDI, PTA, and x% NDI / PTA composite photocatalysts in Examples 1 and 2;
[0025] Figure 4 SEM images of a NDI, b PTA, c NDI / PTA composite photocatalysts in Examples 1 and 2;
[0026] Figure 5 . A three-dimensional morphology image in Example 2; b and c scan the thickness of the NDI nanowire along the red line using an atomic force microscope;
[0027] Figure 6 . A three-dimensional morphology image in Example 1; b and c scan the thickness of the PTA nanowire along the red line using an atomic force microscope;
[0028] Figure 7 .Implementation Case 2a UV-visible diffuse reflectance spectrum of the sample; b Tauc plot of the sample; c Mott-Schottky plot of NDI; d Mott-Schottky plot of PTA;
[0029] Figure 8 . In implementation case 2, a NDI and b PTA work function (WF) were measured using a Kelvin probe;
[0030] Fig. 9 Example 1, 2a NDI / PTA photocatalyst hydrogen production activity diagram with different DNI loadings, b co-catalyst Pt loading hydrogen production activity diagram, c 8% NDI / PTA optimal catalyst dosage photocatalyst hydrogen production activity diagram;
[0031] Fig.10 . Implementation Cases 2, 3 8% NDI / PTA catalyst and Example 5 hydrogen evolution wavelength dependence and apparent quantum efficiency (AQY);
[0032] Fig.11 .Example 2, 3 8% NDI / PTA photocatalyst hydrogen production stability diagram;
[0033] Fig.12 .8% NDNI / PTA fresh sample and used a XRD pattern; b FT-IR spectrum; c SEM image of used 8% NDNI / PTA;
[0034] Fig.13 . a Degradation rate of ofloxacin in different samples in Example 5; b Degradation rate;
[0035] Fig.14 Example 5: Degradation rate of tetracycline hydrochloride by different samples a; degradation rate b;
[0036] Fig.15 Example 5: Degradation rate of sulfamethoxazole by different samples a; degradation rate b;
[0037] Fig.16 In Example 5, a ofloxacin; b tetracycline hydrochloride; c ultraviolet wavelength scanning of sulfamethoxazole solution at different degradation times;
[0038] Fig.17 . LC-MS spectrum of OFL photocatalysis in Example 7;
[0039] Fig.18 Total ion chromatogram (TIC) during OFL photocatalytic degradation in Example 7;
[0040] Fig.19 .OFL photocatalytic degradation pathway in Example 6. DETAILED DESCRIPTION
[0041] The above and other technical features and advantages of the present invention are described in more detail below in conjunction with the accompanying drawings.
[0042] Example 1
[0043] A method for preparing an organic semiconductor PTA comprises the following steps:
[0044] Weigh 50 mg of 3,4,9,10-perylenetetracarboxylic dianhydride into a 250 ml beaker, add 150 ml of ultrapure water to the beaker, and sonicate for 30 minutes with an amplitude of 40 Hz; weigh 500 mg of potassium hydroxide and add it to the above sonicated solution; put the solution into a 50°C water bath and stir for 4 hours to obtain a transparent yellow-green solution; add 500 μl of glacial acetic acid to a 250 ml beaker containing 50 ml of ultrapure water; add the PTA precursor obtained after alkaline hydrolysis with potassium hydroxide to the glacial acetic acid solution, after 8 hours of acidic self-assembly, filter the solid and wash it three times with ultrapure water, and bake it in an oven at 80°C for 2 hours to obtain 3,4,9,10-perylenetetracarboxylic acid (PTA).
[0045] Depend on Figure 2 From the XRD, it can be seen that the XRD spectrum of PTA is indexed to the monoclinic structure, and its diffraction peaks 17.2, 22.8, 30.1 are attributed to the (002), (021) and (500) crystal planes. The peak at the center position of 22.8° corresponds to the π-π stacking of PTA, and its distance is Depend on Figure 3 FT-IR shows that at 1685, 1587 and 1284 cm -1 The stretching vibrations at correspond to the C=O, C=C and CH functional groups of PTA. Figure 4 It can be seen that PTA is an irregular block. Figure 6 It can be seen that the thickness of PTA is about 184.4nm. The above tests prove the successful preparation of organic semiconductor PTA and obtain its microscopic morphology characteristics.
[0046] The addition amount of the photocatalyst PTA is 10 mg, the addition amount of the sacrificial agent ascorbic acid (AA) is 0.2 M (final concentration), the loading amount of the co-catalyst Pt on PTA is 5.0 wt %, and the rest is carried out according to the process and conditions of Example 3. When glacial acetic acid is used, the obtained PTA hydrogen evolution performance is 5.5 mmol / g / h.
[0047] Comparative Example 1
[0048] An organic semiconductor PTA catalyst and a preparation method thereof, comprising the following steps:
[0049] 1) Weigh 50 mg of 3,4,9,10-perylenetetracarboxylic dianhydride into a container, add 150.0 ml of ultrapure water, and perform ultrasound for 30.0 min at an ultrasound amplitude of 40.0 Hz;
[0050] 2) Weigh 500.0 mg of potassium hydroxide and add it to the above ultrasonic solution; stir it at 50° C. for 4.0 h to obtain a PTA precursor;
[0051] 3) Add 500.0 μl of hydrochloric acid (mass concentration 36-38%) to 50.0 ml of water;
[0052] 4) adding the PTA precursor obtained in step 2) after alkaline hydrolysis with potassium hydroxide to the hydrochloric acid solution obtained in step 3) to obtain PTA after 8 hours of acidic self-assembly;
[0053] 5) Solid-liquid separation, washing the solid with water, and drying to obtain PTA.
[0054] The addition amount of the photocatalyst PTA is 10 mg, the addition amount of the sacrificial agent ascorbic acid (AA) is 0.2 M (final concentration), the loading amount of the co-catalyst Pt on PTA is 5.0 wt %, and the rest is carried out according to the process and conditions of Example 3. When hydrochloric acid is used, the obtained PTA hydrogen evolution performance is 1.3 mmol / g / h.
[0055] Comparative Example 2
[0056] An organic semiconductor PTA catalyst and a preparation method thereof, comprising the following steps:
[0057] 1) Weigh 50 mg of 3,4,9,10-perylenetetracarboxylic dianhydride into a container, add 150 ml of ultrapure water, and perform ultrasound for 30 min at an amplitude of 40 Hz;
[0058] 2) Weigh 500.0 mg of potassium hydroxide and add it to the above ultrasonic solution; stir it at 50° C. for 4.0 h to obtain a PTA precursor;
[0059] 3) Add 500.0 μl of phosphoric acid (mass concentration 85%) to 50 ml of water;
[0060] 4) adding the PTA precursor obtained in step 2) after alkaline hydrolysis with potassium hydroxide to the phosphoric acid solution obtained in step 3) to obtain PTA after 8 hours of acidic self-assembly;
[0061] 5) Solid-liquid separation, washing the solid with water, and drying to obtain PTA.
[0062] The addition amount of the photocatalyst PTA is 10 mg, the addition amount of the sacrificial agent ascorbic acid (AA) is 0.2 M (final concentration), the loading amount of the co-catalyst Pt on PTA is 5.0 wt %, and the rest is carried out according to the process and conditions of Example 3. When phosphoric acid is used, the obtained PTA hydrogen evolution performance is 2.4 mmol / g / h.
[0063] Example 2
[0064] A method for preparing a Z-type heterojunction composite organic semiconductor x% NDI / PTA, such as Figure 1 As shown, a composite organic semiconductor x% NDI / PTA was prepared by alkaline hydrolysis and acidic self-assembly, including the following steps:
[0065] Weigh 50 mg of 3,4,9,10-perylenetetracarboxylic dianhydride in a 250 ml beaker, add 150 ml of ultrapure water to the beaker, and ultrasonicate for 30 min at an amplitude of 40 Hz; weigh 500 mg of potassium hydroxide and add it to the above ultrasonicated solution; put the solution in a 50°C water bath and stir for 4 hours to obtain a transparent yellow-green solution, i.e., the precursor of PTA; weigh 2, 4, 8, 16, and 24 mg of NDI (1,4,5,8-naphthalenetetracarboxylic acid diimide) respectively and add it to a 250 ml beaker containing 500 μl of glacial acetic acid and 50 ml of ultrapure water, and ultrasonicate for 1 hour at an amplitude of 40 Hz to obtain an acidic NDI aqueous solution; add the PTA precursor to the acidic NDI aqueous solution, stir in a constant temperature water bath at 40°C for 8 hours, filter the solid and wash it 3 times with ultrapure water, and bake the solid in an oven at 80°C for 2 hours. The obtained catalyst is recorded as: 4% NID / PTA (4% represents that NDI is 4% of the mass (wt%) of PTA), 8% NDI / PTA (8% represents that NDI is 8% of the mass (wt%) of PTA), 16% NDI / PTA (16% represents that NDI is 16% of the mass (wt%) of PTA), 24% NDI / PTA (24% represents that NDI is 24% of the mass (wt%) of PTA), 32% NDI / PTA (32% represents that NDI is 32% of the mass (wt%) of PTA), 48% NDI / PTA (48% represents that NDI is 48% of the mass (wt%) of PTA).
[0066] Depend on Figure 2 The XRD test shows that the characteristic diffraction peaks of x% NDI / PTA with different NDI mass ratios can match the characteristic diffraction peaks of NDI and PTA, indicating the successful preparation of the composite catalyst. Figure 3 By comparing the Fourier transform infrared spectra of NDI and PTA, the characteristic band C=N (1102cm -1 ) and NH(3071cm -1 ) can be found, once again confirming the successful preparation of NDI / PTA. Figure 4 It can be seen that irregular nano-block particles NDI with a size of about 1 μm are loaded on the surface of irregular nano-sheets PTA with a size of about 1 nm. Figure 5 It can be found that the thickness of NDI is about 849.1nm. The above tests prove the successful preparation of the Z-type heterojunction composite catalyst NID / PTA. In order to determine the formation of a Z-type heterojunction between NDI and PTA, the band structures of NDI and PTA were studied by ultraviolet visible diffuse reflectance spectroscopy (UV-Vis DRS) and Mott-Schottky test, such as Figure 7 As shown. Passed the UV visible diffuse reflection test Figure 7a, the absorption ranges of PTA, NDI and x% NDI / PTA were determined and converted using the Kubelka-Munk function to obtain Figure 7 b, calculated band gaps of NDI and PTA are 2.74 and 1.91 eV respectively. The Mott-Schottky equations of NDI and PTA were obtained by electrochemical tests. Figure 7 As shown in c and d, the conduction band (CB) positions of NDI and PTA are -0.61V and -0.42V, respectively (relative to NHE, pH = 7). From the Mott-Schottky test, it can be seen that both NDI and PTA have positive slopes, and the positive slope represents that they are n-type semiconductors. For n-type semiconductors, the flat band potential is approximately the conduction band potential. Combining the calculated band gap value and the measured CB position, the band structure of NDI and PTA is a Z-type electron transfer channel. In other words, under light irradiation, the photogenerated electrons at the CB of NDI are transferred through the interface to the VB of PTA to recombine with the photogenerated holes. At the same time, the spatially separated electrons at the CB in PTA and the holes at the VB in NDI can undergo reduction and oxidation reactions, respectively. In order to further prove the interfacial electron transfer between NDI and PTA, the work function (WF) of NDI and PTA was measured using a Kelvin probe equipped with an atomic force microscope (KPFM), as shown in Figure 2. Figure 8 As shown in a and b, the work functions of NDI and PTA can be calculated to be 4.4 eV and 4.1 eV, respectively. It can be seen that when NDI and PTA are in close contact, electrons spontaneously transfer from NDI to PTA through the heterojunction interface until their Fermi levels reach equilibrium.
[0067] Example 3
[0068] The photocatalytic hydrogen production reaction conditions of the x% NDI / PTA catalyst prepared in Example 1 (PTA catalyst) and Example 2 are both: tested in a glass-enclosed gas system (Labsolar-6A, Beijing Perfectlight).
[0069] First, 10 mg of catalyst powder was added to a reaction tank and ultrasonically dispersed in 100.0 mL of water. Chloroplatinic acid was added to the reaction system, and chloroplatinic acid (H2PtCl6·6H2O) was photocatalytically oxidized to Pt as a co-catalyst on the surface of the composite catalyst by an in-situ photodeposition method. The amount of the co-catalyst added was determined according to the amount of the composite catalyst added in the photocatalytic reaction container during photocatalytic hydrogen production. The amount of the co-catalyst Pt added to PTA or x% NDI / PTA was 1 wt%, and the amount of the sacrificial agent ascorbic acid (AA) added was 0.2 M (final concentration) to determine the loading ratio of NDI, such as Fig. 9As shown in a, the loading mass of NDI relative to PTA is 2%, 4%, 8%, 16%, 24%, 32%, and 48%, respectively. A xenon lamp visible light is used as the light source (420 < λ < 780 nm). The generation of H2 is detected by taking a sample once every 30 minutes through an online gas chromatograph (TCD detector, Ar carrier, 5 μm molecular sieve column) for a total test time of 3 hours.
[0070] Next, 10 mg of 8% NDI / PTA catalyst powder was added to the reaction tank and ultrasonically dispersed in 100.0 mL of water. The sacrificial agent ascorbic acid (AA) was added in an amount of 0.2 M (final concentration). Chloroplatinic acid was added to the reaction system, and chloroplatinic acid (H2PtCl6·6H2O) was photocatalytically oxidized to Pt as a co-catalyst on the surface of the composite catalyst by an in-situ photodeposition method. The amount of co-catalyst added was determined according to the amount of composite catalyst added in the photocatalytic reaction vessel during photocatalytic hydrogen production. The loading amount of the co-catalyst Pt relative to the 8% NDI / PTA catalyst was determined as follows: 0.5, 1.0, 3.0, 5.0, 7.0, 9.0 wt% Fig. 9 b. A 300W xenon lamp with visible light was used as the light source (420<λ<780nm). The generation of H2 was detected by an online gas chromatograph (TCD detector, Ar carrier, 5μm molecular sieve column) with a sampling time of 30 minutes for a total test time of 3 hours.
[0071] Finally, 1, 2, 3, 5, 7, 10, 15, and 20 mg of 8% NDI / PTA catalyst powder were ultrasonically dispersed in 100.0 mL of water, and the sacrificial agent ascorbic acid (AA) was added in an amount of 0.2 M (final concentration). Chloroplatinic acid was added to the reaction system, and chloroplatinic acid (H2PtCl6·6H2O) was photocatalytically oxidized to Pt as a co-catalyst on the surface of the composite catalyst by an in situ photodeposition method. The loading amount of the co-catalyst Pt relative to the 8% NDI / PTA catalyst was 5.0 wt%. The optimal amount of the catalyst 8% NDI / PTA was determined as follows: Fig. 9 c. A 300W xenon lamp with visible light was used as the light source (420<λ<780nm).
[0072] The generation of H2 was detected by an online gas chromatograph (TCD detector, Ar carrier, 5 μm molecular sieve column) with a sampling time of 30 minutes for a total test time of 3 hours.
[0073] First, the optimal loading amount of NDI was determined. Test conditions: the photocatalyst addition amount was 10 mg, the sacrificial agent addition amount was 0.2 M, and the co-catalyst was loaded at 1.0% of the main catalyst addition amount. Fig. 9It can be seen that with the increase of NDI content, the catalytic performance of DNI / PTA gradually improves. With the increase of NDI content, the catalytic performance gradually improves. When the loading mass of NDI relative to PTA is 8%, the H2 evolution performance of NDI / PTA is the best, which is 13.50mmol / g / h. When the mass of NDI continues to increase, the performance of NDI / PTA begins to decline slightly. This is mainly due to the fact that the heterostructure formed at the interface between NDI and PTA can effectively separate the photogenerated carriers. Although the heterostructure formed at the interface between NDI and PDA can effectively separate the photogenerated carriers, the excess NDI will make the interface between NDI and PTA unable to absorb enough light. There is a balance between charge separation and light absorption, and 8% NDI / PTA may be the balance point. The right amount of ND can enhance the separation of photon-generated carriers and improve the catalytic activity, while the excess NDI will mask PTA, resulting in a decrease in catalytic activity. It is PTA that plays a leading role in the composite photocatalyst. The gradual increase of NDI will lead to a decrease in PTA, which will also reduce the photocatalytic activity.
[0074] Fig. 9 b The optimal loading amount of the co-catalyst Pt was determined. The test conditions were: 10 mg of 8% NDI / PTA main catalyst and 0.2 M sacrificial agent ascorbic acid were added to the photocatalytic hydrogen production test system. The amount of co-catalyst added was 0.5, 1, 3, 5, 7, and 9 wt% according to the loading amount on 10 mg of the main catalyst. The deposition amount of Pt was studied by reducing H2PtCl6·H2O to Pt as a co-catalyst loaded on the photocatalyst through in-situ photodeposition using H2PtCl6·H2O aqueous solution. The photocatalytic hydrogen evolution performance increased continuously with the loading amount of Pt from 0.5-5wt%, and 5wt% of Pt had the highest H2 evolution rate. The photocatalytic hydrogen evolution performance decreased with the continued increase in the loading amount of Pt from 5wt% to 9wt%, because too much Pt has a shielding effect, which hinders the absorption of light by the photocatalyst. In addition, although Pt can provide active sites for hydrogen evolution, excessive Pt will over-aggregate on the surface of the photocatalyst, causing some of the original active sites on the surface of the photocatalyst to be covered or occupied by Pt particles.
[0075] Fig. 9 c Determine the optimal amount of catalyst. The test conditions are: the amount of co-catalyst Pt added is 5wt%, and the amount of sacrificial agent ascorbic acid added is 0.2M. When the amount of 8% NDI / PTA increases from 1mg to 2mg, the photocatalytic hydrogen evolution performance increases to 45.56mmol / g / h. When the amount of 8% NDI / PTA continues to increase, the hydrogen evolution performance decreases. The reason may be that the catalyst shields the light, causing the lower catalyst to be unable to absorb light energy, which in turn leads to a decrease in the photocatalytic hydrogen evolution performance.
[0076] Example 4
[0077] The stability test of the 8% DNI / PTA catalyst prepared in Example 2. Test conditions: 10 mg of the 8% DNI / PTA catalyst was ultrasonically dispersed in 100.0 mL of water, chloroplatinic acid was added to the reaction system, and chloroplatinic acid (H2PtCl6·6H2O) was photocatalytically oxidized to Pt as a co-catalyst on the surface of the composite catalyst by an in-situ photodeposition method. The co-catalyst Pt was added in an amount of 5 wt% of the 8% DNI / PTA catalyst, and the amount of sacrificial ascorbic acid added was 0.2 M (final concentration). The cycle was repeated every 5 hours, and samples were taken every 30 minutes. Fig.11 It can be seen that the catalyst has good stability. The hydrogen evolution performance of the catalyst can maintain a high level within 50 hours. After 20 hours, the hydrogen evolution performance of the catalyst gradually decreases. The reason is that the sacrificial agent ascorbic acid is exhausted. Then, the 8% NID / PTA catalyst after about 50 hours of testing was tested by XRD, FT-IR, and TEM. Fig.12 As shown in the figure, it can be seen that there is no obvious change in the catalyst before and after use, which indicates that the catalyst has good stability and recyclability during the photocatalytic reaction.
[0078] Example 5
[0079] The apparent quantum efficiency (AQY) of the 8% NDI / PTA catalyst prepared in Example 2 was measured under different bandpass filters and different monochromatic lights (365nm, 400nm, 450nm, 500nm, 550nm, 600nm, 650nm and 700nm). The irradiation area was 1cm -2 (300W xenon lamp, PerfectLight). The average intensity was determined by an optical power meter (PL-MW2000). 7 mg of photocatalyst was used.
[0080] 8% NDI / PTA hydrogen evolution wavelength dependence and apparent quantum efficiency (AQY) Fig.10 The good agreement between the light absorption and AQY in different wavelength regions indicates that the H2 evolution reaction is indeed a photoinduced process. In addition, the AQY of 8% NDI / PTA at 450nm is 3.16%, which is much higher than most reported organic semiconductor photocatalysis.
[0081] Example 6
[0082] The photocatalytic degradation reaction conditions of the NDI catalyst, Example 1 (PTA catalyst), and Example 2 prepared by x% NDI / PTA are all: using a 300W xenon lamp (420<λ<780nm) to continuously simulate sunlight irradiation for photocatalytic degradation research. The photodegradation reaction was carried out in a double-jacketed quartz tube reactor using 10mg of 8% NDI / PTA catalyst and 100mL of antibiotic (ofloxacin, ofloxacin, tetracycline hydrochloride) solution (20mg L -1 ) suspension. The reaction temperature was maintained at 20°C by a circulating cooling water system in the jacket. Before light irradiation, the suspension was stirred in the dark for 30 minutes to reach adsorption-desorption equilibrium. Every 10 minutes, the solution was drawn from the reaction tank through a needle filter (13 mm, 0.54 μm) to obtain the supernatant, which was analyzed by liquid ultraviolet (UV-VIS SPECTROPHOTOMETER T9) to obtain the degradation rate and degradation rate of different antibiotics.
[0083] Experiment on photocatalytic degradation of ofloxacin (OFL). Fig.13 As shown in the figure, after 90 min of irradiation, the removal rate of OFL by 8% NDI / PTA reached 81%, and the degradation rate (0.021 min -1 ) is NDI (0.0006min -1 ) is 35 times that of PTA (0.01min -1 ) is 2.1 times the degradation rate of ofloxacin under light without catalyst, and 70 times the degradation rate of ofloxacin under light without catalyst.
[0084] The photocatalytic degradation of tetracycline hydrochloride (TC-HCl) was carried out as follows Fig.14 As shown in the figure, the removal rate of TC-HCl by 8% NDI / PTA is as high as 86.5%, and the degradation rate (0.018min -1 ) is NDI (0.0001min -1 ) is 180 times that of PTA (0.014min -1 ) is 1.3 times the rate of tetracycline hydrochloride degradation under light without catalyst.
[0085] Experimental study on photocatalytic degradation of sulfamethoxazole (SMX) Fig.15 As shown in Figure 2, the photocatalyst can also degrade SMX. Within 90 minutes, the removal rate of 8% NDI / PTA was 21%, and the degradation rate (0.0026min -1 ) is NDI(0.0002min -1 ) is 13 times that of PTA (0.0013min -1 ) and is 12 times the rate of degradation of sulfamethoxazole under light without catalyst.
[0086] The catalyst prepared in Example 2 was subjected to UV full spectrum scanning of antibiotics with different degradation times according to the test method of Example 5. Fig.16 As shown, it can be seen that with the extension of photocatalytic time, the characteristic diffraction peak intensity of OFL and TC-HCl decreased significantly, and the characteristic diffraction peak intensity of SMX also decreased. In addition, no new absorption peaks appeared during the degradation process, indicating that photocatalysis effectively degraded these three antibiotics. The characteristic diffraction peaks of OFL and TC-HCl almost disappeared, indicating that their molecular structures have been destroyed. This shows that most of the antibiotics in the solution have been degraded at this time, resulting in the weakening of the absorption peak of the characteristic diffraction peak.
[0087] Example 7
[0088] Ultra-high performance liquid chromatography-electrostatic field orbital trap high-resolution mass spectrometry (LTQOrbitrap XL) was used to measure the intermediates of OFL degradation using 8% NDI / PTA catalyst in Example 5. A C18 chromatographic column (Waters, USA) was used for chromatographic separation. The mobile phases A and B were methanol and water containing 0.1% formic acid by volume, respectively. The eluent (mobile phase) flow rate was 0.3 mL / min, the injection volume was set to 5 μ, and the column temperature was 40°C. The mobile phase gradient program started with A: B 10 / 90 (v / v) and lasted for 1 minute, then A linearly increased to A: B = 95 / 5 within 5 minutes and maintained for 1 minute, and then returned to A: B = 10 / 90 for 2 minutes. A positive ionization electrospray interface was used. Electrospray ionization was controlled at 4 kV and the N2 flow rate was 12 L / min.
[0089] like Fig.17 As shown in Figure 2, a total of 16 intermediates were detected. Total ion chromatogram (TIC) of OFL degradation Fig.18 As shown in the figure, the untreated OFL solution only showed one OFL peak with a retention time of 4.55 minutes. After 30 minutes of reaction, many product peaks appeared, and the retention times of these peaks were 7.07 minutes, 7.13 minutes, 7.59 minutes, 7.88 minutes, 8.13 minutes, 8.46 minutes, etc. As time went by, these product peaks gradually decreased and disappeared after 90 minutes, indicating that the OFL and intermediate products produced during the reaction gradually decomposed into inorganic substances.
[0090] The possible degradation pathways of the intermediate products obtained by testing the catalyst prepared in Example 2 according to the method of Example 6 are speculated, such as Fig.19 As shown in the figure, there are four possible pathways for the photocatalytic degradation of OFL by 8% NDI / PTA. In the first possible pathway, the degradation of OFL begins with the cleavage of the tetrahydropyridine ring and the detachment of the ethyl group to generate the intermediate product P1 (m / z=339). Subsequently, the N42 atom on the piperazine ring is catalyzed by the action of h+ , and then P2 is attacked and demethylated to generate P2 (m / z=296). P2 is then separated from the carboxyl, carbonyl and methyl groups to generate P3 (m / z=182). The second possible pathway is that ofloxacin is subjected to ring opening, deethylation and methyl separation to generate P5 (m / z=325). Then, P5 is separated from the methyl group to generate P6 (m / z=311), and P6 is separated from the carboxyl, amino, ethyl and methyl groups to generate P7 (m / z=226). P7 is then separated from the ring, amino, carbonyl and methyl groups to obtain P8 (m / z=163). Finally, P8 is separated from the fluorine and opened to form P4 (m / z=121). The third possible pathway is First, the tetrahydropyridine of OFL is attacked, followed by ring opening, ethyl and methyl separation to generate P9 (m / z=296). Then, P9 is separated by methyl, amino, ethyl and hydroxyl to generate P10 (m / z=223), and P10 is separated by fluorine, amino, carboxyl and ring opening to generate P11 (m / z=149). The fourth possible pathway is that OFL is separated by ring opening, methyl, ethyl and hydroxyl to generate P12 (m / z=319). P12 is then separated by amino, carbonyl and methyl to generate P13 (m / z=277), and P13 is separated by methyl to obtain P14 (m / z=263). Then, P14 undergoes a series of oxidation reactions to generate P15 (m / z=87). Finally, these small molecules are oxidized and decomposed into CO2 and H2O, thereby achieving the purpose of degrading OFL.
[0091] The above description is only the preferred embodiment of the present invention, which is only illustrative and not restrictive. Those skilled in the art understand that many changes, modifications, and even equivalents can be made to the present invention within the spirit and scope defined by the claims of the present invention, but they will all fall within the scope of protection of the present invention.
Claims
1. A Z-type heterojunction bifunctional composite photocatalyst NDI / PTA, characterized by: In the composite catalyst NDI / PTA (1,4,5,8-naphthalenetetracarboxylic acid diimide / 3,4,9,10-perylenetetracarboxylic acid), NDI accounts for 1.0-30.0% (preferably 2.0-30.0%, more preferably 3.0-18.0%, and optimally 3.7-9.0%) of the mass (wt%) of PTA.
2. A method for preparing the composite catalyst NDI / PTA according to claim 1, the specific process being: 1) Weigh 50 mg of 3,4,9,10-perylenetetracarboxylic dianhydride into a container, add 150.0-300.0 ml of water to obtain a solution; 2) Weighing 400.0-600.0 mg (preferably 420.0-580.0 mg, more preferably 450.0-550.0 mg, and optimally 490.0-510.0 mg) of potassium hydroxide, adding it to the solution of step 1); stirring it at 40.0-55.0° C. for 2.0-4.0 h to obtain a precursor of 3,4,9,10-perylenetetracarboxylic acid PTA; 3) Weighing 0.5-25.0 mg of NDI (1,4,5,8-naphthalenetetracarboxylic acid diimide) (preferably 2.0-16.0 mg, more preferably 2-8.0 mg, optimally 3-5 mg) and adding it to 50.0-100.0 ml of water containing 400.0-600.0 μl (preferably 400.0-600.0 μl, more preferably 450.0-550.0 μl, optimally 490.0-510.0 μl) of glacial acetic acid to obtain an acidic NDI aqueous solution; 4) Add the PTA precursor to the NDI acidic aqueous solution at 35.0-45.0°C (preferably 35.0-45.0°C, optimally 37.0-42.0°C) and stir for 6-10 hours; 5) solid-liquid separation, washing the solid with water, and drying to obtain the NDI / PTA composite catalyst.
3. The preparation method according to claim 2, characterized in that: In step 1), 50 mg of 3,4,9,10-perylenetetracarboxylic dianhydride is weighed into a container, 150.0-300.0 ml of water is added, and ultrasonic treatment is performed for 30.0-60.0 min at an ultrasonic amplitude of 40.0-100.0 Hz; In step 3), NDI is weighed and added to water containing glacial acetic acid, and ultrasonicated for 1.0-2.0 h with an ultrasonic amplitude of 40-100 Hz to obtain an acidic aqueous solution of NDI.
4. Use of the composite catalyst NDI / PTA according to claim 1 in photocatalytic water decomposition to produce hydrogen.
5. The use according to claim 4, characterized in that: The application conditions are as follows: 1.0-20.0 mg (preferably 5.0-13 mg, optimally 9.0-11.0 mg) of composite catalyst powder is ultrasonically dispersed in 100.0 mL of water; chloroplatinic acid is added into the reaction system, and chloroplatinic acid (H2PtCl6·6H2O) is photocatalytically oxidized to Pt as a promoter on the surface of the composite catalyst by an in-situ photodeposition method, wherein the amount of the promoter added is determined according to the amount of the composite catalyst added in a photocatalytic reaction container during photocatalytic hydrogen production, and the mass loading of the promoter (in terms of Pt) relative to the composite catalyst is 0.5-9.0 wt% (preferably 1.0-8.0 wt%, more preferably 3-6 wt%; optimally 4.0-6.0 wt%); 0.15-0.3 M ascorbic acid (AA) is used as a sacrificial agent, and xenon lamp visible light is used as a light source (420<λ<780 nm).
6. Use of the composite catalyst NDI / PTA according to claim 1 in the degradation process of one or more of the antibiotics ofloxacin, tetracycline hydrochloride and sulfamethoxazole.
7. The use according to claim 6, characterized in that: The application conditions are as follows: using a xenon lamp (420<λ<780nm) for photocatalytic degradation, using 5.0-13.0mg (preferably 5.0-13mg, optimally 9.0-11.0mg) of photocatalyst and 100mL of antibiotic solution with an antibiotic concentration of 10.0-50.0mg / L (preferably 10.0-40.0mg / L, more preferably 15.0-30mg / L, optimally 17.0-22.0mg) for reaction; the reaction temperature is maintained at 20-25°C.
8. The use according to claim 7, characterized in that: Before light irradiation, the suspension was stirred in the dark for more than 30 min to reach adsorption-desorption equilibrium.
Citation Information
Patent Citations
Method for preparation of composite photocatalyst from photosensitizer and use thereof
CN104248977A
Carboxyl-containing perylene bisimide / oxygen-doped carbon nitride nanosheet heterojunction photocatalyst as well as preparation method and application thereof
CN111389458A
Preparation method of bay-site substituted perylene bisimide photocatalytic water decomposition catalyst
CN117659012A
PERYLENE TETRACARBOXYLIC ACID BISIMIDE DERIVATIVE, n-TYPE SEMICONDUCTOR, PROCESS FOR PRODUCING n-TYPE SEMICONDUCTOR, AND ELECTRONIC DEVICE
EP2695885A1